Penguatan Peran Masyarakat dalam Mendukung Keberlanjutan Operasi Rumah Pompa untuk Mitigasi Banjir di Kabupaten Sampang - Moh Makmun; Eny Haryati; Aris Sunarya; Ika Devy Pramudiana (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2025)
This research discusses the strengthening of community roles in supporting the sustainability of pump house operations as an effort for flood mitigation in Sampang Regency. The frequent floods in this area are caused by geographical factors and an inadequate drainage system. This study aims to explore the active role of the community in the management and maintenance of pump houses. The method used in this research is a descriptive qualitative approach, with data collection through interviews, surveys, and observations. The findings indicate that community participation in monitoring the condition of the pump houses and maintenance activities significantly contributes to the effectiveness of flood mitigation. However, there are still challenges regarding the community's understanding of the functions and importance of pump houses. The implications of this study recommend enhancing education and socialization to the community to increase their involvement in the sustainability of pump house operations, which is crucial in reducing flood risks in the future.